Comparison of sonographically guided vacuum-assisted and automated core-needle breast biopsy methods [Meme lezyonlarinda US kilavuzlugunda vakum destekli biyopsi (mamotom) ve "tru-cut" biyopsi yöntemlerinin karşilaştirilmasi.] - (:unkn) unknown (My University, 2004)
PURPOSE: To compare the diagnostic accuracy and complication rates of sonographically guided vacuum-assisted and automated core-needle breast biopsy methods. MATERIALS AND METHODS: Sonographically guided biopsy was performed in 125 solid breast lesions found at mammography and observed at ultrasonography. Vacuum-assisted biopsy was performed in 61 lesions, while automated core-needle biopsy was performed in 64 lesions. The lesions with a benign histological diagnosis were followed radiologically. Those lesions with a histological diagnosis of malignancy or atypical ductal hyperplasia underwent surgical treatment. RESULTS: In the vacuum-assisted biopsy group, 62.3% of the lesions were totally removed. Four lesions in vacuum-assisted biopsy group and two lesions in the automated core-needle biopsy group were diagnosed as atypical ductal hyperplasia histologically. Of the 4 BI-RADS category lesions, three lesions from each group were noted to be malignant. Histological results were not significantly different between the two groups (p>0.05). In both groups, lesions diagnosed as atypical ductal hyperplasia or malignancy showed no difference in the histological diagnosis after excisional biopsy. Complication rates were not significantly different between the two biopsy methods (p>0.05). CONCLUSION: No significant difference was found between sonographically guided vacuum-assisted and automated core-needle breast biopsy methods in terms of diagnostic accuracy and complication rates. However, vacuum-assisted biopsy can be preferred for total removal of the benign lesions.